Modernization and Effeminization in India: Kerala Cashew Workers since 1930 - Anna Lindberg (NIAS Press, 2004)
The South Indian state of Kerala is well known for its progressive policy, high social indicators, and comparatively high women's status. Processes of modernization, however, have had an ambiguous impact on women there. This paper traces changes since the 1930s in gender relations among low-caste men and women in Kerala by examining processes of modernization in the organization of work, trade union activities, and ideologies regarding marriage and family life. Female cashew workers, who number something between 200,000 and 400,000, form the majority of the factory workers in the state. Most of them have been organized into trade unions since the 1940s or 50s. They are literate and throughout their history they have been very militant-if we measure militancy in terms of man-days lost due to strikes. They seem to contrast strongly with "Third World Women", who are often portrayed as illiterate, ignorant, and tradition-bound victims. Although the female cashew workers of Kerala have obtained better absolute conditions at work and in society, the power 2 discrepancy between low-caste men and women has increased in favor of men because low-caste women are now seen as weaker and more dependent on men than in earlier decades. "Modernization", intensified capitalism, and various ideologies and discourses-whether emanating from the West or constructed locally-have increased the gap between masculinity and femininity. The concept effeminization of women is here introduced to denominate a process discernable at different levels in the productive and reproductive spheres that, in contrast to feminization, is qualitative, ideological, and discursive.